Beyond technonationalism : biomedical innovation and entrepreneurship in Asia - Ibata-Arens, Kathryn C. (Innovation and technology in the world economy., 2019)
Asia is currently on track to become the epicenter of growth in biopharmaceuticals and medical devices. This book accounts for the regional rise of these industries with a conceptual framework that considers how national governments have managed key factors, like innovative capacity, government policy, and the firm-level strategies in China, India, Japan, and Singapore. What emerges is an argument that countries which encouraged a global mindset in these target industries, while pursuing a more traditional, nationalistic agenda within the domestic economy, have been most successful.